“Constructal Human Dynamics, Security and Sustainability” - Miguel, A. F. (2012)
Globalization, security infrastructure and energy sustainability can be designed based on a scientific principle. In this book, these objectives are approached based on constructal theory, which means to design such projects as global flow architectures that are alive with movement of personnel, equipment, information, education, etc. Constructal Human Dynamics, Security and Sustainability highlights the progress made during the NATO Advanced Research Workshop held in Évora, Portugal in May 2008. This workshop brought together social scientists with physicists, engineers and biologists. Together they addressed main topics such as human dynamics viewed as natural phenomena of design generation, flow networks for distribution and collection, large-scale construction projects (e.g., airports, waste storage), logistics, decontamination, energy supply routes, distributed energy systems, water resources management, environmental security sustainability and globalization. The chapters selected for this book represent the interdisciplinary approach.